Pengembangan Model Game Based Learning Berbasis Permainan Ular Tangga dalam Penjas - Fermina; Ade Rahmat; Ashadi Cahyadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The aim of this study was to develop a game-based learning model for physical education based on the game of snakes and ladders. The study employed the Research and Development (R&D) method using the ADDIE model. The target clientele for the product includes: (1) elementary school Physical Education, Sports, and Health (PJOK) teachers; (2) elementary school students; and (3) the general public. Validation results from subject-matter and media experts yielded an average score of 93.6%, placing the model in the “highly feasible” category. Practicality tests involving teachers indicated that the model was easy to implement in physical education lessons, while students found the game more engaging than conventional instruction. Effectiveness testing showed an average score increase of 18.70 points following implementation of the snakes-and-ladders-based game-based learning model. Based on these findings, it can be concluded that the model meets the criteria of validity, practicality, and effectiveness, making it a suitable alternative learning model for physical education. Keywords: Games Based Learning, Physical Education, Snakes and Ladders